2017
DOI: 10.1103/physrevphyseducres.13.020132
|View full text |Cite
|
Sign up to set email alerts
|

Students’ conceptual difficulties in hydrodynamics

Abstract: We describe a study on the conceptual difficulties faced by college students in understanding hydrodynamics of ideal fluids. This study was based on responses obtained in hundreds of written exams and oral interviews, which were held with first-year Engineering and Science university students. Their responses allowed us to identify a series of misconceptions unreported in the literature so far. The study findings demonstrate that the most important difficulties arise from the students' inability to establish a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 16 publications
1
23
0
9
Order By: Relevance
“…Even the physics of ideal fluids has revealed misconceptions, and difficulties encountered by students in classical hydrodynamics (Bernoulli's equation) have been reported in detail [57]. This paper corroborates several misconceptions on pressure and velocity in ideal fluids and naive interpretations of Bernoulli's equation, and includes a valuable (though incomplete) bibliography.…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicssupporting
confidence: 67%
See 2 more Smart Citations
“…Even the physics of ideal fluids has revealed misconceptions, and difficulties encountered by students in classical hydrodynamics (Bernoulli's equation) have been reported in detail [57]. This paper corroborates several misconceptions on pressure and velocity in ideal fluids and naive interpretations of Bernoulli's equation, and includes a valuable (though incomplete) bibliography.…”
Section: Work In Progress In Learning and Teaching Fluid Mechanicssupporting
confidence: 67%
“…Another example developed in [57] refers to the flow of liquids in a contraction; a common misconception claims that the greater the velocity is, the greater the pressure will be. Several studies indicate that, for students, either liquids are compressible or pressure is a force and force is linked to velocity and not to acceleration, a typical misconception in the FCI.…”
Section: Targeted Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ada beberapa miskonsepsi utama yang dialami siswa pada konsep prinsip bernoulli yaitu kecepatan aliran fluida sebanding dengan tekanannya atau semakin besar kecepatan fluida maka semakin besar tekanannya dan debit aliran fluida (v) berbanding terbalik dengan luas penampang pipa (Recktenwald et al, 2010;Saputra et al, 2020;Suarez et al, 2017). Beberapa hasil penelitian menjelaskan alasan terjadi-nya miskonsepsi pada konsep tersebut yaitu siswa beranggapan bahwa tekanan sama dengan gaya sehingga mereka kemudian menghubungkan konsep gaya dengan kecepatan dari percepatan (Saputra et al, 2020).…”
Section: Pendahuluanunclassified
“…Difficulties related to Archimedes' principle have been revealed by Loverude et al (2003), Wagner et al (2013), and Kusairi et al (2020). In the context of dynamic fluid, Suarez et al (2017) revealed students' failure to integrate the continuity equation and Bernoulli's law. This indicates that facilitating students to master essential concepts of fluid is not an easy matter.…”
Section: Introductionmentioning
confidence: 99%